Proteomic analysis of rice mutant pir1 reveals molecular mechanisms triggering PCD and conferring high resistance to bacterial blight - Chen, Xinyu; Zhou, Yujie; Liang, Weifang; Zhou, Yuhang; Xie, Liujie; Hou, Fan; Zheng, Bingsong; Li, Jianzhong (Frontiers in Plant Science, 2025)
Most rice mutants exhibit some level of resistance to bacterial blight. This study demonstrates that the rice lesion mimic mutant (LMM) pir1 possesses enhanced resistance to bacterial leaf blight and triggers the upregulation of multiple pathogenesis-related (PR) proteins. Concurrently, photosynthetic parameter measurements revealed a significant impairment in the photosynthetic electron transport chain and photosynthetic capacity in pir1. Assessments of various stress factors and electron microscopy observations indicated that accumulated reactive oxygen species (ROS) caused severe damage to plant organelles. Utilizing proteomic approaches, we analyzed differentially expressed proteins (DEPs) between pir1 and its wild-type counterpart. Two-dimensional fluorescence difference gel electrophoresis (2D-DIGE) combined with mass spectrometry (MS) analysis of different leaf positions from both materials identified a total of 321 DEPs, comprising 87 upregulated and 234 downregulated proteins. Bioinformatics analysis of these DEPs revealed their involvement in diverse biological processes, including photosynthesis, carbohydrate metabolism, defense responses, redox homeostasis, and energy metabolism. Analysis of the regulatory network suggests that the mutation pir1 participates in programmed cell death (PCD), thereby triggering disease resistance responses.